Antibacterial ferroelectric materials: Advancements and future directions - Kumar, Sandeep; Sharma, Moolchand; Frömling, Till; Vaish, Rahul (Journal of industrial and engineering chemistry (Seoul, Korea), 2021)
[Display omitted] Ferroelectric functional materials are known for a wide range of applications including sensors, actuators, energy harvesting devices. Very recent studies based on ferroelectric materials for environmental cleaning and bacterial remediation add a further up-and-coming field of application of these materials. They possess several advantages over conventional methods such as biocompatible range and sustainability. Although the research area is relatively new, some substantial experimental work has been done in the last couple of years. The rationale and underlying mechanisms of different published reports were compiled and explained to offer a better understanding of the subject. The three major mechanisms can be divided into catalysis via a change in surface potential, mediated catalysis by the formation of reactive oxide species on the ceramic surface due to piezoelectric or pyroelectric excitation, and enhanced photocatalysis due to internal electric fields. Our goal is to provide a comprehensive report on ferroelectric materials application in the prevention of bacterial infections and to give an outlook on further possible research strategies.